IPv6+ innovation of the NGI - Hui TIAN; Zheng WEI (Dianxin kexue, 2020)
Nowadays,experts in the field of internet have reached a consensus that the deployment of IPv6 is not the whole of the next generation internet,but the starting of the next generation internet innovation.The requirements of cloud convergence and 5G application scenarios were analyzed,the functions and performance requirements of typical application scenarios were combed,and the IPv6+ technology innovation of the next generation internet was summarized.